Faticidade e historicidade: a proto-religiosidade cristã como chave interpretativa da experiência fática da vida - Ferrandin, Jairo (2010)
This work intends to resume the project of a phenomenological explanation of the Pauline letters concerning the original experience of primitive Christianity, drawn up by Heidegger in his course Einleitung in die Phänomenologie der Religion, in 1920-21. In it, the philosopher seeks to develop new means of access to religious phenomenon based on the notion of experience of life in its factual historicity. This is new reappropriation of tradition, not in the sense of objectivity and the repetition of content, theories and doctrines, but the destruction, which allows reconnecting from the experiences of the generation sense. The notion of facticity permeates all the peculiar characteristics that encompass the initial thought of Heidegger, particularly during their first academic activities. Will also enable the construction of new concept of philosophy, known originally as science or as hermeneutics of facticity, with sense and concepts - the formal indication - that distinguish the ideals of scientific objectivity. The resumption of Heidegger's project also has the intent to highlight how the religious and Christian theology occupied a central place in the early development of the question of the sense of being, and what their possible contributions and directions decisive for the discussion of key issues generated the basic ideas of Sein und Zeit